Science and mathematics teachers of the future - Michelsen, Claus (2008)
This paper presents the project Science and Mathematics Teachers of the Future. The aim of the project is to develop and implement a graduate level equivalent degree program in mathematics and science instruction for in-service teachers of lower secondary education. This aim is achieved in the programme through involving the teachers in design, implementation and evaluation of innovative instructional sequences, which deals with a wide range of aspects of mathematics and science, e.g. modern science and the importance of science in society. In the program contemporary science and mathematics education research serves as a basis for the design and development of warranted practices with which the teachers may experiment in their classroom. We will focus on the outcomes of offering a program which is intimately tied to (i) contemporary science and mathematics education research, (ii) modern science and mathematics and (iii) the teacher’s practices in the classroom.